Exploring EFL Students’ Writing Strategies in Composing Classroom Action Research (CAR) Proposals - Afdalia, Tiara; Fauzan, Akhmad; Bahing, Bahing (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
This study explored the writing strategies employed by EFL students when composing Classroom Action Research (CAR) proposals, focusing on the frequency of strategy use. Using a quantitative research design, data were collected through a structured questionnaire administered to 48 undergraduate students in the English Language Education Study Program at the University of Palangka Raya. The questionnaire measured the frequency of pre-writing, while-writing, and revising strategies. The findings reveal that students frequently engaged with while-writing strategies, particularly translation from Indonesian to English. The pre-writing stage showed moderate engagement, with students commonly reviewing examples of well-written proposals but less frequently using formal outlining techniques. In the revising stage, feedback from lecturers was highly valued, with students actively using it to improve their proposals. However, self-editing strategies were less emphasized, indicating a reliance on external feedback for revisions. The study concludes that while students benefit from translation and feedback-driven revision, there is a need for more significant support in developing independent revision skills and expanding academic vocabulary.